Recurrent Chronic Subdural Hematoma: Clinical and Imaging Risk Factors - Abdennebi, Benaissa; Al Shamiri, Maher (Indian Journal of Neurotrauma, 2018)
Background Chronic subdural hematoma (CSDH) is a major cause of neurosurgical emergencies in the elderly. Despite the use of routine surgical practices, recurrence of this condition is expected. This study was conducted to identify the risk factors (RF) for recurrent CSDH.Methods Between January 2016 and July 2017, 103 consecutive patients suffering from CSDH were admitted to our department. The no-recurrence group (NRG) consisted of 91 patients, and the recurrence group (RG) consisted of 12 patients. To identify the RF involved in recurrent CSDH, we analyzed multiple factors, including patient comorbidities and imaging data.Results Between the two groups, there were no statistical differences (p > 0.05) for head trauma, diabetes mellitus (DM), high blood pressure, heart diseases, anticoagulation agents, or seizures; however, DM was associated with one of the above-mentioned factors. In contrast, there were significant differences for antiplatelet agents (APA) (p < 10–6) and the right side of the hematoma location (p = 0.03).Conclusion Although the literature highlights the controversy regarding RF for CSDH, we detected APA and the right side as RF, whereas DM alone or associated with another comorbidity does not affect the CSDH outcome.
Keywords: chronic subdural hematoma; recurrence; risk factor; diabetes mellitus; comorbidity